Sectoral impacts of international labour migration and population ageing in the Czech Republic - Martin Stepanek (Charles University in Prague, Institute of Economic Studies (IES), 2019)
This study assesses macroeconomic and sectoral impacts of demographic changes in the Czech Republic, as a result of population ageing and international migration. To do so, it develops a unique dynamic Overlapping Generations Computable General Equilibrium (OLG-CGE) model with detailed representation of individuals of different ages, educational attainment and occupations, as well as interrelations among industrial sectors in producing intermediate and final outputs. The numeric simulations show that the Czech economy will face a substantial reduction in its effective labour supply and changes in sectoral demand patterns, leading to an increase in unit labour costs and consequent shift towards more capitalbased production, price increase for the consumers, and a long-term decrease in demand particularly for agricultural products. While international migration may alleviate the pressure, the annual net immigration would need to increase by at least 8 thousand individuals on average in the 2020-2035 period and by 17 thousand individuals in the 2036-2050 period to offset the negative effects in the long term.
Keywords: C68; E27; J11; 330; OLG; CGE; migration; labour force; economic impact